Effect of catchment-scale green roof deployment on stormwater generation and reuse in a tropical city - Schmitter, Petra S.; Goedbloed, A.; Galelli, S.; Babovic, V. (American Society of Civil Engineers, 2016)
Low-impact development (LID) comprises a broad spectrum of stormwater management technologies for mitigating the impacts of urbanization on hydrological processes. Among these technologies, green roofs are one of the most adopted solutions, especially in densely populated metropolitan areas, where roofs take up a significant portion of the impervious surfaces and land areas are scarce. While the in situ hydrological performance of green roofs—i.e., reduction of runoff volume and peak discharge—is well addressed in literature, less is known about their impact on stormwater management and reuse activities at a catchment or city scale. This study developed an integrated urban water cycle model (IUWCM) to quantitatively assess the effect of uniform green roof deployment (i.e., 25, 50, and 100% conversion of traditional roofs) over the period 2009–2011 in the Marina Reservoir catchment, a 100-km2, highly urbanized area located in the heart of Singapore. The IUWCM consists of two components: (1) a physically based model for extensive green roofs integrated within a one-dimensional numerical hydrological-hydraulic catchment model linked with (2) an optimization-based model describing the operation of the downstream, stormwater-fed reservoir. The event-based hydrological performance of green roofs varied significantly throughout the simulation period with a median of about 5% and 12% for the catchment scale reduction of runoff volume and peak discharge (100% conversion of traditional roofs). The high variability and lower performance (with respect to temperate climates) are strongly related to the tropical weather and climatic conditions—e.g., antecedent dry weather period and maximum rainfall intensity. Average annual volume reductions were 0.6, 1.2, and 2.4% for the 25, 50, and 100% green roof scenarios, respectively. The reduction of the stormwater generated at the catchment level through green roof implementation had a positive impact on flood protection along Marina Reservoir shores and the energy costs encountered when operating the reservoir. Vice versa, the drinking water supply, which depends on the amount of available stormwater, decreased due to the evapotranspiration losses from green roofs. Better performance in terms of stormwater reuse could only be obtained by increasing the time of concentration of the catchment. This may be achieved through the combination of green roofs with other LID structures.